Encephalitis, Mild Encephalitis, Neuroprogression, or Encephalopathy—Not Merely a Question of Terminology - Bechter, Karl (Frontiers in Psychiatry, 2019)
Background: Psychoneuroimmunology research has presented emerging evidence of the involvement of inflammatory and immune mechanisms in the pathogenesis of severe mental disorders. In this context, new terms with increasing clinical relevance have been proposed, challenging the existing terms, and requiring consensus definitions of the new ones. Method: From a perspective of longstanding personal involvement in clinical settings and research in psychoneuroimmunology, the new and the existing terms are critically reconsidered. Results: Meningoencephalitis and encephalitis are comparably well defined clinical terms in neuropsychiatry, although in the individual case approach diagnosis can be difficult, for example in some cases of encephalitis that are described with normal cerebrospinal fluid findings, or often in chronic encephalitis. Encephalopathy is also a widely accepted term, however, with a surprisingly broad meaning with regard to the assigned underlying pathophysiology, ranging from one-hit traumatic encephalopathy to inflammatory encephalopathy, the latter term addressing a type of brain dysfunction secondary to acute systemic inflammation without proven brain autochthonus inflammation (neuroinflammation). However, this latter assumption and term may be wrong as neuroinflammation is difficult to prove in vivo. With emerging insights into prevailing inflammatory and neuroinflammatory mechanisms that are involved in the pathogenesis of severe mental disorders, the interdependent aspects of sensitive assessment and potential clinical relevance of mild neuroinflammation are becoming more apparent and of increasing clinical interest. The new terms “mild encephalitis,” “parainflammation,” and “neuroprogression” show considerable overlap in addition to gaps and hardly defined borders. However, details are hard to discuss as available studies use many biomarkers, but most of these are done without an established categorical attribution to exclusive terms. Most important, the three new concepts (neruoprogression, parainflammation, and mild encephalitis) are not mutually exclusive, even at the individual case level, and therefore will require state-related individual assessment approaches beyond large confirmatory studies. Conclusion: The newly proposed terms of mild encephalitis, parainflammation, and neuroprogression have an emerging clinical relevance, but respective borders, gaps and overlap in between them remain unclear, and these concepts may even be seen as complementary. Categorical delineation of the new and reconsideration of the existing terms with respect to individualized psychiatric treatment is required for better clinical use, eventually requiring a consensus approach. Here, a critique based on available data and a focus on clinical perspective was outlined, which may help to enhance fruitful discussion. The idea followed here is in line with pillar number six as proposed for the Research Diagnostic Domains, i.e., to provide and follow new concepts in psychiatric research.